Urolithin M5 from the Leaves of Canarium album (Lour.) DC. Inhibits Influenza Virus by Targeting Neuraminidase - Xiao, Mengjie; Cao, Fei; Huang, Tao; Tang, Yun-Sang; Zhao, Xin; Shaw, Pang-Chui (Molecules (Basel, Switzerland), 2022)
Ganlanye (GLY), the leaf of Canarium album (Lour.) DC., is a traditional Chinese medicinal herb for warm disease treatment. We found that its aqueous extract could inhibit the influenza A virus. To find and characterize anti-influenza virus phytochemicals from GLY, we performed (1) bioassay-guided isolation, (2) a cell and animal assay, and (3) a mechanism study. Bioassay-guided isolation was used to identify the effective components. Influenza virus-infected MDCK cell and BALB/c mouse models were employed to evaluate the anti-influenza virus activities. A MUNANA assay was performed to find the NA inhibitory effect. As a result, urolithin M5 was obtained from the crude extract of GLY. It inhibited influenza virus activities in vitro and in vivo by suppressing the viral NA activity. In the MDCK cell model, urolithin M5 could inhibit an oseltamivir-resistant strain. In a PR8-infected mouse model, 200 mg/kg/d urolithin M5 protected 50% of mice from death and improved lung edema conditions. GLY was recorded as a major traditional herb for warm disease treatment. Our study identified GLY as a potent anti-influenza herb and showed urolithin M5 as the active component. We first report the in vivo activity of urolithin M5 and support the anti-influenza application of GLY.